Heavy Metals (Cu, Pb and Cd) in Water and Angel Fish (Chelmon rostractus) from Batam Coastal, Indonesia - Ismarti Ismarti; Ramses Ramses; Suheryanto Suheryanto; Fitrah Amelia (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
Fish play an important role in human nutrition and therefore need to be carefully and routinely monitored to ensure that there are no high levels of heavy metals being transferred to human through their consumption. This study has been carried out to determine level of heavy metals (Cu, Pb, and Cd) in water and angel fish, Chelmon rostractus collected from coast of Batam. We report levels of Cu, Cd and Pb in water and angel fish from Coast Batam using Atomic Absorption Spectroscopy (AAS). Level of heavy metals obtained in water and fishes were fluctuative. Cu was obtained in both, water and fish muscles. Level of Cu in fishes muscle still under the permissible limit, but it was exceeded permissible limit for water. Cd not detected in water, but it was obtained in fish muscles. Level of Cd in fishes from Tanjung Pinggir site was exceeded permissible limit. High level of Pb was found in water and fish muscles. Level of Pb in water and fish muscles were exceeded permissible limit. It is indicated that the coast Batam has contaminated with Cu, Pb and Cd. Key words: heavy metals, angel fish, marine pollution, Batam coastal